Canadian Music and American Culture
VIII, 297 p.
Keywords: This collection explores Canadian music’s commentaries on American culture. ‘American Woman, get away from me!’ - one of the most resonant musical statements to come out of Canada - is a cry of love and hate for its neighbour. Canada’s close, inescapable entanglement with the superpower to the south provides a unique yet representative case study of the benefits and detriments of the global American culture machine. Literature scholars apply textual and cultural analysis to a selection of Anglo-Canadian music – from Joni Mitchell to Peaches, via such artists as Neil Young, Rush, and the Tragically Hip – to explore the generic borrowings and social criticism, the desires and failures of Canada’s musical relationship with the USA. This innovative volume will appeal to those interested in Music, Canadian Studies, and American Studies.